CORPORATE GOVERNANCE DAN FINANCIAL DISTRESS PADA KECEPATAN PUBLIKASI LAPORAN KEUANGAN - Budiasih, I Gusti Ayu Nyoman; Saputri, P. Dwi Aprisia (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2014)
This study aims to determine the effect of corporate governance consisting of independent board, auditÃ‚Â committee, managerial ownership and institutional ownership, and financial distress on speed publication offinancial statements. This study uses data on manufacturing companies listed in Indonesia Stock ExchangeÃ‚Â in 2012-2014. The samples in this study use a non-probability sampling with purposive sampling aproach. Thenumber of observations in this study is 102 samples of the study. The data analysis technique used is multipleÃ‚Â linear regression analysis. Based on the analysis it is concluded that the independent board, audit committee,institutional ownership, and financial distress has no effect on the speed of publication of financial statements.Ã‚Â While the managerial ownership gives a positive effect on the speed of publication of financial statements.Keywords: corporate governance, financial distress, publication speed,managerial ownership